Enhancement of the cancer inhibitory effect of the bioactive food component resveratrol by nanoparticle based delivery. Issue 4 (26th March 2020) - Bano, Sameena; Ahmed, Faheem; Khan, Farha; Chaudhary, Sandeep Chand; Samim, M.
Abstract : Enhanced chemo-preventive effect of nanoresveratrol on skin tumorigenesis in mouse by suppressing inflammatory responses and oxidative stress and inducing apoptosis. Abstract : Naturally occurring bioactive food components such as dietary polyphenols have shown many beneficial biological activities due to their good antioxidant properties. Among them significant attention has been given to resveratrol (RV) in recent years as it plays a promising role in cancer prevention. It has demonstrated anti-proliferative effects, as well as the ability to inhibit the initiation and progression of induced cancer in a wide variety of tumor models. However, the benefits of its therapeutic effects were found to be limited due to its poor pharmacokinetic properties such as poor aqueous solubility, instability and extensive first pass metabolism. To overcome these limitations, the present study aimed to synthesize thermosensitive copolymeric nanoparticle encapsulated formulations of resveratrol–nanoresveratrol (NRV) and evaluate their in vitro anticancer activity and inhibitory effect on 12-O-tetradecanoylphorbol-13-acetate (TPA)-promoted skin inflammation and tumorigenesis in Swiss albino mice. For this purpose PNIPAAM-PEG based thermosensitive copolymeric nanoparticles were synthesized followed by the encapsulation of RV in their hydrophobic core. This enhanced the therapeutic bioavailability of resveratrol. Nanoresveratrol demonstrated stronger antioxidant activity and comparable anticancer efficacy to free resveratrol. Nanoparticles were characterized by IR, NMR, DLS and TEM. The best results were obtained with NRV at significantly lower doses. NRV demonstrated better in vitro anticancer activity against melanoma cell line B16. It showed comparable reduction of TPA induced skin edema, hyperplasia and oxidative stress response. In the promotion phase, a significant reduction was found in tumor incidence and tumor burden in mice pre-treated with NRV. Moreover, at all doses NRV altered Bax and Bcl2 expressions which lead to the induction of apoptosis.